Model'no-tselevoi sposob postroeniya sportivnoi podgotovki vysokokvalifitsirovannykh sportsmenov v zimnykh tsiklicheskikh vidakh sporta - Batalov, A. G. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
The author of this paper considering available opportunities and problems in realization of the model-purpose approach to construction of speedskiers sports preparation. - precondition of modeling of purpose competitive activity of the speedskiers; - opportunity of the settlement forecasting the sport-technical result in ski races; - modeling of the external individual parameters of competitive activity; - modeling of the internal parameters of purpose competitive activity.